Social Safety Nets in Iraq : Reform in a Time of Fragility, Conflict, and Violence - Alkhoja, Ghassan; Neman, Ramzi; Hariz, Sara (World Bank, Washington, DC, 2016)
Iraq, once a relatively skilled and economically prosperous society, has seen its development thwarted by decades of conflict and economic decline. Today it is an upper middle-income, resource-rich, yet fragile and conflict-riven country. Progress on the twin goals of ending extreme poverty and boosting shared prosperity is inevitably an uphill struggle in such a context. Indeed, there has been no overall movement towards either poverty reduction or reduced income equality in Iraq since 2007; headcount poverty measured in 2014 has remained virtually unchanged at 22.5 percent. What limited gains in poverty reduction were achieved through 2012 had been reversed by 2014, as a result of a resurgence in violence and the worsening of the economic environment. More than four million Iraqis have been displaced by the country’s various conflicts.